Inklusi Agama di Tempat Ibadah dan Dampaknya terhadap Konsep Diri dan Dukungan Psikososial di Kalangan Penyandang Disabilitas di Bandung - Wasik, Abdul; Muttaqin, Zaenal; Permana, Fadhila Sidiq (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2025)
This study examines how inclusion in houses of worship shapes self-concept and psychosocial support among people with disabilities in Bandung, while also identifying accessibility barriers and the role of disability organizations. Using a qualitative design with purposive sampling, the study engaged people with disabilities, religious leaders, community members, and disability advocates, and conducted observations across 32 mosques. Data were collected through in-depth interviews, participant observation, and document review, then analyzed using thematic coding. The findings indicate that religious experiences can foster self-acceptance and a more positive self-concept, and provide meaningful emotional and psychological support through gratitude, hope, and community reinforcement. Nevertheless, religious participation remains constrained by inadequate physical accessibility, communication barriers (especially the need for sign language), limited access to inclusive religious education (e.g., braille or tailored assistance), and social isolation intertwined with economic constraints such as transportation costs. The study also reveals that religion is not always the primary driver of change; rather, it often functions as a form of metamotivation after basic needs are met, while group solidarity more frequently emerges from shared disability experiences and organizational support. The study implies the need to strengthen accessibility standards in houses of worship, expand sign-language services and braille/disability-friendly materials, and enhance collaboration between local government, religious institutions, and disability organizations to create safe, equitable, and psychosocially supportive worship environments. The originality of this research lies in linking worship-place inclusion, religious metamotivation, and psychosocial support within an urban Bandung setting through multi-site observation.